2013
DOI: 10.1186/1746-1596-8-73
|View full text |Cite
|
Sign up to set email alerts
|

Sudden, unexpected death due to glioblastoma: report of three fatal cases and review of the literature

Abstract: Sudden death from an undiagnosed primary intracranial neoplasm is an exceptionally rare event, with reported frequencies in the range of 0.02% to 2.1% in medico-legal autopsy series and only 12% of all cases of sudden, unexpected death due to primary intracranial tumors are due to glioblastomas. We present three cases of sudden, unexpected death due to glioblastoma, with different brain localization and expression. A complete methodological forensic approach by means of autopsy, histological and immunohistoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…Akyıldız et al found primary cause of death with malignant tumors with a lower rate (0.25%) in a study conducted in Istanbul Turkey (18). However the age and sex distribution of this study was similar with literature of cancer (8)(9)(10).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Akyıldız et al found primary cause of death with malignant tumors with a lower rate (0.25%) in a study conducted in Istanbul Turkey (18). However the age and sex distribution of this study was similar with literature of cancer (8)(9)(10).…”
Section: Discussionsupporting
confidence: 88%
“…Malignancies could also be found incidentally in medico-legal autopsies (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). In the present study such kind of malignancies was found 2.1 % in 3722 medicolegal autopsy cases in which histopathological examination was performed.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The clinical picture of GBM depends on several aspects: the location of the tumor and adjacent structures involved in tumor expansion, the rhythm of tumor progression, the marked invasive behavior, a hallmark for GBM, bleeding -either within the tumor (glioblastomas are strongly vascularized tumors, with an impressive potential of neoangiogenesis), or bleeding in other vascular structures secondarily involved in the extending -infiltrative lesion, the existence of multifocal lesions, patient age and comorbidities. There have been reported cases with atypical clinical features such as ulnar neuropathy, syncopal events [93], or even sudden unexpected death [88]. The progress of medical imaging tools, today owning a remarkable degree of accuracy in describing different types of lesions, decreased the importance of a thorough clinical approach in order to establish the topography of the tumor.…”
Section: Epidemiology Clinical Features and Imagingmentioning
confidence: 99%